Non-pharmacological treatment of arterial hypertension in primary care: An integrative review (Research, Society and Development, 2021)
Objective: Analyze the tools used in the non-drug treatment of systemic arterial hypertension in the context of primary care. Method: It is an Integrative Literature Review in which bibliographic survey was used as a methodological resource on the following platforms: Lilacs, Medline, CVSP, Scielo as well as the Google Scholar platform, adding scientific studies covered between the years 2015 to 2020. In this bibliographic survey carried out over the internet the descriptors were used: Arterial Hypertension, Non-pharmacological Treatments and Primary Care. Results and Discussion: Based on the studies used in this research, it was found that non-pharmacological treatments have a valuable importance for the therapy of systemic arterial hypertension, even reflecting the prevention of diseases in patients with risk factors and comorbidity. Conclusion: It was allowed to understand that non-pharmacological treatments have positive effects, but need continuous monitoring, taking into account the social context and personal difficulties of each individual.